2013
DOI: 10.1016/j.jep.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Propolis and its constituent caffeic acid suppress LPS-stimulated pro-inflammatory response by blocking NF-κB and MAPK activation in macrophages

Abstract: Propolis and its constituent caffeic acid suppress LPS-stimulated pro-inflammatory response by blocking NF-κB and MAPK activation in macrophages, Journal of Ethnopharmacology, http://dx.doi.org/ 10. 1016/j.jep.2013.06.004 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 47 publications
7
111
0
2
Order By: Relevance
“…Our results show that propolis lowers the inflammatory response through a diminished expression of the TLR4 pathway. Búfalo et al (2013) did report the antiinflammatory effect of propolis by holding back the unphosphorylated IκBα and down-regulating NF-κB, central to the inflammatory cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that propolis lowers the inflammatory response through a diminished expression of the TLR4 pathway. Búfalo et al (2013) did report the antiinflammatory effect of propolis by holding back the unphosphorylated IκBα and down-regulating NF-κB, central to the inflammatory cascade.…”
Section: Discussionmentioning
confidence: 99%
“…actions have been demonstrated, like antioxidant (Frozza et al, 2013), anti-nociceptive (Franchin et al, 2012), and anti-inflammatory (Búfalo et al, 2013;Szliszka et al, 2013). These activities are linked to its bioactive compounds and it is noteworthy that propolis from different geographic regions can vary significantly in its chemical composition (López et al, 2014;Piccinelli et al, 2011;Sawaya et al, 2011).…”
Section: Propolis Extracts Have Received Great Interest In Medicine Amentioning
confidence: 99%
“…Recent studies demonstrated that Chlorogenic Acid, Isochlorogenic Acid A, Isochlorogenic Acid B and Isochlorogenic Acid C could attenuate the release of PGE 2 and IL-6 in macrophage Shan et al, 2009). Caffeic Acid suppressed LPS-stimulated pro-inflammatory response in RAW264.7 cells (Bufalo et al, 2013;Uwai et al, 2008). However, to date, no scientific study has been done on the combination effects of the compounds in RDN.…”
Section: Discussionmentioning
confidence: 99%